2017
DOI: 10.3390/cryst7120355
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Calcium Carbonate in Alginate and Xanthan Hydrogels

Abstract: Calcium carbonate polymorphs were crystallized in alginate and xanthan hydrogels in which a degree of entanglement was altered by the polysaccharide concentration. Both hydrogels contain functional groups (COOH and OH) attached at diverse proportions on saccharide units. In all systems, the precipitation process was initiated simultaneously with gelation, by the fast mixing of the calcium and carbonate solutions, which contain the polysaccharide molecules at respective concentrations. The initial supersaturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Therefore, there was no need to eliminate CaCO 3 crystals in order to form the pores, and even vice versa, the crystals have been kept in the final scaffold architecture. A straightforward approach for the fabrication of composite CaCO 3 -alginate gel materials was first employed nearly one decade ago and has been based on the simultaneous growth of CaCO 3 crystals and gelation of alginate hydrogel [138,139,140,141,142]. In this design, calcium carbonate crystals grow in the presence of the gel and get entrapped inside this polymer matrix.…”
Section: Vaterite Caco3-assistant Porous Alginate Scaffolds (Pas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there was no need to eliminate CaCO 3 crystals in order to form the pores, and even vice versa, the crystals have been kept in the final scaffold architecture. A straightforward approach for the fabrication of composite CaCO 3 -alginate gel materials was first employed nearly one decade ago and has been based on the simultaneous growth of CaCO 3 crystals and gelation of alginate hydrogel [138,139,140,141,142]. In this design, calcium carbonate crystals grow in the presence of the gel and get entrapped inside this polymer matrix.…”
Section: Vaterite Caco3-assistant Porous Alginate Scaffolds (Pas)mentioning
confidence: 99%
“…), the final distribution of crystals and the macrostructure of the scaffold cannot be controlled since the crystallization of CaCO 3 is a spontaneous and highly sensitive process. In addition, the presence of calcite and sometimes amorphous calcium carbonate has been detected [139]. For some cases, a significant decrease in the size of CaCO 3 crystals resulted in the formation of nano-CaCO 3 that found its application in drug delivery but was not suitable for the fabrication of macro-porous scaffolds [141].…”
Section: Vaterite Caco3-assistant Porous Alginate Scaffolds (Pas)mentioning
confidence: 99%
“…Previous studies suggested that the prismatic shapes of travertine calcite crystals are related to crystalline lattice and growth morphologies being affected by impurities, concentrations of Mg, phosphate or sulphate, high fluid supersaturation with respect to carbonates, and presence of microbial biofilms (Folk et al, 1985; Folk, 1993, 1994; Tracy et al, 1998; Bosak and Newman, 2005; Di Benedetto et al, 2011; Jones and Peng, 2014a; Jones, 2017a). Numerous experimental studies on the precipitation of carbonate crystals confirm that crystal morphology is influenced by the presence of impurities, hydrogels, polymers and various organic molecules (Gower and Tirrell, 1998; Falini et al, 2000; Meldrum and Hyde, 2001; Kato et al, 2002; Cölfen, 2003; Oaki and Imai, 2003; Chekroun et al, 2004; Tong et al, 2004; Bosak and Newman, 2005; Sand et al, 2011; Keller and Plank, 2013; Tobler et al, 2014; Kosanović et al, 2017). Konopacka-Lyskawa et al (2017) showed that calcite crystal morphology changes from scalenohedral to rhombo-scalenohedral elongated crystals and crystal size decreases at increasing organic compound concentrations.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The study gave a better explanation of the influence of silk fibroin concentration and its structure on CaCO 3 crystals’ growth. Nindiyasari et al investigated the influence of the porosity of the growth medium on the crystallization of CaCO 3 in hydrogels with different gelatin solid contents [ 14 ], whereas Kosanović et al crystallized CaCO 3 polymorphs in alginate and xanthan hydrogels in which the degree of entanglement was altered by the polysaccharide concentration [ 15 ]. Crystallization experiments performed in alginate hydrogels indicated the initial formation of a mixture of calcite, vaterite and amorphous CaCO 3 .…”
Section: Basic Researchmentioning
confidence: 99%